Comparative study between natural and synthetic Hydroxyapatite: structural, morphological and bioactivity properties - Sossa, Paola Andrea Forero; Giraldo, Belarmino Segura; Garcia, Beatriz Clemencia Galviz; Parra, Elisabeth Restrepo; Arango, Pedro Jose Arango (Matéria, 2018)
ABSTRACT In this work, a study of hydroxyapatite (HAp) powders obtained using both, porcine bones and chemical precursors was carried put. In the case of HAp obtained by means of porcine bones, physical processes as cooking, washing and milling were developed, for removing the organic material from the bones; after that, the powders were submitted to a thermal treatment at 800 °C, during 12 h. This procedure was carried out without adding chemical alkalines that are harmful for the environment and the human health. On the other hand, HAp powders were also synthetized using the chemical precipitation method widely reported, showing successful results. Moreover, both kind of powders were characterized using x ray diffraction, Fourier transformer infrared spectroscopy, scanning electron microscopy and energy dispersive spectroscopy. Furthermore, the bioactivity of the materials was determined using the simulated biological fluid (SBF) method. Results showed that the natural HAp exhibited better crystallographic properties. Moreover, according to these results, HAp obtained from porcine bones contains traces of elements as Na and Mg that are favorable for the bioactivity, according to the materials behavior when they are immersed in SBF.